(untitled) (Journal of Academic Research, 2025)
In this paper, a simulation model for an incremental relative quadrature encoder is designed based on sine function and developed to generate standard quadrature signals usually called phases A and B, the model is programed or built up by using Matlab-Simulink enviro-nment. Consequently, 1x and 4x resolution decoder algorithms are designed and developed to decode the incremental signals generated by the encoder simulator. Together, the encoder and the decoder algorithms are combined to construct and emulate a realistic rotary incremental angular position sensor. The sensor emulator is used in closing the loop of feedback angular position servo control systems, to test the impact of incremental sensors on the performance of the feedback servo control systems, and to assess the effect of the sensor resolution on the error between the desired value and the actual output of the system not the measured one. Finally, the developed algorithms in the form of Matlab-Simulink models are compiled and implemented successfully to control a simple real angular position servo control system with a very low resolution sensor in real time.